2012
DOI: 10.1097/nen.0b013e31825b5f7a
|View full text |Cite
|
Sign up to set email alerts
|

Polysomy of Chromosomes 1 and/or 19 Is Common and Associated With Less Favorable Clinical Outcome in Oligodendrogliomas

Abstract: It is well established that the combined del(1)(p36) and del(19)(q13) is a positive prognostic molecular event in oligodendroglial tumors. However, very little is known about the frequency or impact of polysomy status for chromosomes 1/19. We examined 84consecutive pure oligodendrogliomas (68 World Health Organization [WHO] grade II and 16 WHO grade III) and analyzed them for del(1)(p36) and del(19)(q13) by fluorescent in situ hybridization. Polysomy status was recorded with accompanying deletion status, WHO g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 6 publications
5
23
0
Order By: Relevance
“…Similarly, a lower occurrence of 19p polysomy was observed in WHO grade II gliomas. It was consistent with Wiens et al [14] report which maintained that polysomies of chromosomes 1 and/or 19 were slightly more common in high-grade tumors (56 % of AO vs. 42 % of O) and co-polysomy was significantly correlated with higher histologic tumor grade (P = 0.04).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, a lower occurrence of 19p polysomy was observed in WHO grade II gliomas. It was consistent with Wiens et al [14] report which maintained that polysomies of chromosomes 1 and/or 19 were slightly more common in high-grade tumors (56 % of AO vs. 42 % of O) and co-polysomy was significantly correlated with higher histologic tumor grade (P = 0.04).…”
Section: Discussionsupporting
confidence: 92%
“…But the frequency of 1q and 19p polysomy was significantly higher in mixed glioma compared with OGDs or astrocytic tumors. In 2012, Wiens et al [14] analyzed 84 consecutive pure oligodendrogliomas and found that the 1q and 19p polysomy rate was 43 and 36 %, respectively. They concluded that polysomy of 1q and/or 19p was a relatively frequent occurrence in oligodendrogliomas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cutoff value for 3p deletion was defined as a 3p25/CEP3 ratio of r0.7, as previously described. 7,18,[22][23][24] Definitions of chromosomal trisomy of chromosomes 7 and 17 were based on the Gaussian model and related to the nonneoplastic controls. The cutoff values for each probe were set at mean plus three standard deviations (mean þ 3 s.d.)…”
Section: Fishmentioning
confidence: 99%
“…Polysomy is more common in high-than low-grade gliomas [42e45], but data on its prognostic relevance independent of WHO grade are conflicting [44,45]. Few studies have evaluated the significance of polysomy in those with 1p19q co-deletion, with reports of both worse [45,46] and equivalent [21,47,48] survival compared with those without polysomy.…”
Section: Fluorescence In Situ Hybridisation Probe Signal Patterns: Abmentioning
confidence: 99%